Determinants of capital structure in sri lanka: Evidence from panel data - Vijayakumaran, R.; Vijayakumaran, S. (Proceedings of the international conference of Sri Ram Institute of Management Studies, India., 2011)
This study investigates the use and the determinants of long-term leverage using the sample of 50 companies listed in Colombo Stock exchange (CSE). The panel cross sectional regression analysis was performed for 226 firm year observations over the period from 2004 to 2008. The study reveals that at an aggregate level, leverage of Sri Lankan firms is comparatively low. The size of the firms is positively significantly related to leverage while profitability is negatively significantly associated with leverage suggesting that more profitable firms tend to use less leverage. This suggests that firms tend to follow a reverse pecking order with regard to external financing: Equity is the first source of external finance on the pecking order. This study documents that the size and profitability have robust effects on long-term leverage in Sri Lanka.
Keywords: Leverage; market to book ratio; tangibility; profitability